2015
DOI: 10.1039/c4cp04271a
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic crossover in dielectric relaxation behavior of ice Ih

Abstract: The main mechanism of the dielectric relaxation process of ordinary hexagonal ice (ice Ih) and its temperature dependence remains unclear. The most interesting and as yet unexplained feature of ice is the presence of the dynamical crossover in relaxation time behavior around Tc = 230 ± 3 K. Since there are no phase transitions in the ice at this temperature (first or second order), we cannot correlate the origin of this crossover with any structural change. Here we present a model according to which the temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 36 publications
7
52
0
Order By: Relevance
“…The Debye relaxation model given in equation is well suited to describe the dielectric behavior of pure water ice up to several hundreds of MHz [ Johari , ], even if below 250 K a Cole‐Cole model [ Cole and Cole , ] is more suitable [ von Hippel et al, ; Popov et al, ]. Such behavior, essentially due to proton hopping polarization, has been extensively studied by several authors, with major contributions from Bjerrum [], Granicher et al [], Jaccard [], Onsager and Dupuis [], Jaccard [], Nagle [], and Bilgram and Gränicher [].…”
Section: An Overview Of Water Ice Dielectric Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Debye relaxation model given in equation is well suited to describe the dielectric behavior of pure water ice up to several hundreds of MHz [ Johari , ], even if below 250 K a Cole‐Cole model [ Cole and Cole , ] is more suitable [ von Hippel et al, ; Popov et al, ]. Such behavior, essentially due to proton hopping polarization, has been extensively studied by several authors, with major contributions from Bjerrum [], Granicher et al [], Jaccard [], Onsager and Dupuis [], Jaccard [], Nagle [], and Bilgram and Gränicher [].…”
Section: An Overview Of Water Ice Dielectric Propertiesmentioning
confidence: 99%
“…However, below about 230 K two effects are visible: a change in the slope of each curve (excluding Auty and Cole []) and a remarkable divergence between the curves. This behavior has been attributed to the presence of impurities [ Gough and Davidson , ; Kawada , ] or to the interchange in the role of the majority and minority carriers [ Bilgram and Gränicher , ; Popov et al, ] and is still a matter of intense debate.…”
Section: An Overview Of Water Ice Dielectric Propertiesmentioning
confidence: 99%
“…Therefore, we attribute relaxation II to the ice Ih phase whereas (the faster) relaxation I may be related with polarization in the disordered liquid-like surface layers of the ice crystallites [35]. The fact that the time scale of relaxation II shows different temperature dependence than those of bulk hexagonal ice has also been observed in other hydrated systems and reflects, actually, the great sensitivity of the dielectric properties of ice crystallites on their defects and on the impurities that are incorporated in their lattice [34,36]. It is interesting that all of the tissues exhibit relaxations I and II with similar characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In the most cases, the dielectric loss spectra in the presence of the excess wing are described by means of expression at n = 2. So, it has a sense to give the complete expression for relaxation function for this case, as well normalψ(t)=1normalπfalsefalse0extx(normalτ1x)normalα1sinnormalπ(1normalα1)+(normalτ2x)normalα2sinnormalπ(1normalα2)1+(normalτ1x)2normalα1+(normalτ2x)2normalα2+2(normalτ1x)normalα1(normalτ2x)normalα2cosnormalπnormalα2+2(normalτ1x)normalα1cosnormalπnormalα1+2(normalτ2x)normalα2cosnormalπ(normalα1normalα2)dx. In paper with the help of formula at n = 2, it became possible to describe the spectrum of dielectric losses of the hexagonal ice, where the excess wing phenomenon is provided by two independent relaxation mechanisms. The fitting results showed that for the first relaxation mechanism, α 1 =1 and, for the second one, α 2 =α≈0,92.…”
Section: Further Generalizationsmentioning
confidence: 99%
“…In the most cases, the dielectric loss spectra in the presence of the excess wing are described by means of expression (4) at n D 2. So, it has a sense to give the complete expression for relaxation function for this case, as well §.t/ D 1 In paper [26] with the help of formula (4) at n D 2, it became possible to describe the spectrum of dielectric losses of the hexagonal ice, where the excess wing phenomenon is provided by two independent relaxation mechanisms. The fitting results showed that for the first relaxation mechanism, ' 1 D 1 and, for the second one, ' 2 D ' 0, 92.…”
Section: Further Generalizationsmentioning
confidence: 99%